On the estimation of cardinality of common solutions to congruence equation - Mohd Atan, Kamel Ariffin; Sapar, Siti Hasana (2010)
Method of estimating the cardinality of the set of common solution to congruence equation associated with the partial derivative polynomial of two-variable polynomials with integer coefficients will be presented in this talk. The application of the cardinality in determining explicitly an upper bounds of a two-variable exponential sums associated with the polynomial of degree five will be demonstrated.